DEVELOPING AN INTEGRAL INDEX FOR ASSESSING LOCAL PRODUCTION POTENTIAL IN ENSURING REGIONAL FOOD SECURITY (Marketing Jurnali, 2026)
This article developed an integral index for assessing local production potential in ensuring regional food security. The study established a comprehensive system of indicators covering the resource base, production volume and productivity, stability and diversification, as well as market and institutional linkages. Scientific approaches to indicator normalization, weighting, and aggregation were substantiated to ensure reliable index construction. The findings demonstrated opportunities to comprehensively evaluate regional production potential, strengthen food security, improve the quality of managerial decision-making, and enhance the efficient use of available resources. The proposed index also provided a practical methodological tool for monitoring territorial development, supporting evidence-based regional planning, and improving the effectiveness of agricultural and food security management.